THE HUMANIZATION OF IMMIGRATION LAW: THE ROLE OF THE PARALEGAL IN THE FACE OF THE EMOTIONAL AND INFORMATIONAL VULNERABILITY OF THE MIGRANT - Manhães, Marcela; Teixeira, Stephanie (Revista Gênero e Interdisciplinaridade, 2026)
This article presents a systematic literature review on the interface between the immigration legal system and the psychosocial and informational vulnerability of migrants, focusing on the humanizing role of the paralegal. The central objective is to analyze how the work of this professional contributes to mitigating administrative violence, acculturative stress, and information access asymmetries experienced by individuals in transit. The research adopts a systematic methodology based on PRISMA guidelines, with database searches covering the period from 2021 to 2026, complemented by classical theorists from the legal, social and information sciences. The results show that the bureaucratic structure of the immigration system operates as a device of depersonalization and informational exclusion, where procedural uncertainty, structural delays, and legal illiteracy produce acute psychological suffering and amplify systemic inequalities. The paralegal emerges as an essential socio-legal actor and informational mediator, whose functions transcend technical support to encompass communicational mediation, procedural time management, curation of accessible legal information, and the construction of institutional trust. It is concluded that the humanization of immigration law is achieved through everyday practices that recognize the migrant in their entirety, with the paralegal being indispensable for the effectiveness of access to justice and for reducing informational barriers that perpetuate structural vulnerability.